The Readiness of Typical Student in Communication By Using Sign Language in Hearing Impairment Integration Programe - Mohd Hanafi Mohd Yasin; Liong Kon Thai; Nuur Thaqifah Mohd Tahir (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2018)
This research is regarding the readiness of typical student in communication by using sign language in Hearing Impairment Integration Programme. There were 60 typical students from a Special Education Integration Programme of secondary school in Malacca were chosen as research respondents. The instrument of the research was a set of questionnaire which consisted of four parts, namely Student’s demography (Part A), Student’s knowledge (Part B), Student’s ability to communicate (Part C) and Student’s interest to communicate (Part D). The questionnaire was adapted from the research of Asnul Dahar and Rabiah's 'The Readiness of Students in Following Vocational Subjects at Jerantut District, Rural Secondary School in Pahang'. Descriptive analysis was used to analysis the data. Mean score was used to determine the level of respondents' perception of each question. The findings showed a positive relationship between typical students towards communication medium by using sign language. Typical students were seen to be interested in communicating using sign language and were willing to attend the Sign Language class if offered.